CONTENT AND ESSENCE OF PRACTICAL TECHNOLOGIES OF WORKING WITH CHILDREN IN NEED OF INCLUSIVE EDUCATION (European Journal of Interdisciplinary Research and Development, 2026)
This article discusses the professional skills and cooperation of teachers in the Inclusive Education system, first of all, the specific features of working with children with special needs, and the fact that this form of education guarantees equal treatment in all cases for children with disabilities or developmental disabilities, while creating the necessary conditions for children with special educational needs. Today, in our country, large-scale work is being carried out to create inclusive conditions in order to provide children with disabilities and developmental disabilities with quality education and ensure their subsequent decent employment.